2020
DOI: 10.1088/2053-1591/ab6dae
|View full text |Cite
|
Sign up to set email alerts
|

Research on metallurgical bonding of selective laser melted AlSi10Mg alloy

Abstract: The densification behavior, surface morphology and attendant microstructural characteristics of the selective laser melting (SLM) processed AlSi10Mg alloy affected by the processing parameters were systematically investigated. Increasing the laser scanning speed or hatch spacing will deteriorate the metallurgical bonding between melt pools, resulting in the increase of irregular pores. Scanning speed and hatch spacing affect the liquid metallurgical bonding of melt pools in different ways. By manipulating scan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 30 publications
0
3
0
1
Order By: Relevance
“…Samples manufactured by SLM with metallic powder have a higher elastic modulus in the in-plane direction compared with the cross-plane direction [11]. In the manufacturing process, thermal stress accumulates as a result of rapid heating and cooling [34], or flat pores are generated because of the low energy density [35,36] between layers. These defects result in a higher elastic modulus in the in-plane direction than in the cross-plane direction [11,14].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Samples manufactured by SLM with metallic powder have a higher elastic modulus in the in-plane direction compared with the cross-plane direction [11]. In the manufacturing process, thermal stress accumulates as a result of rapid heating and cooling [34], or flat pores are generated because of the low energy density [35,36] between layers. These defects result in a higher elastic modulus in the in-plane direction than in the cross-plane direction [11,14].…”
Section: Resultsmentioning
confidence: 99%
“…Gas is trapped in the pores during manufacturing. Irregular pores are formed between the layers because of the gas contraction force and gravity during rapid heating and cooling [36]. The ellipsoid pores expand because of the high gas temperature.…”
Section: Resultsmentioning
confidence: 99%
“…SLM has several advantages over conventional mechanical manufacturing processes, including design freedom, which enables the production of components with complex shapes that would be difficult to produce using conventional methods (Zou et al, 2019). It improves component strength and density, reduces waste by using the exact amount of material for each layer, and allows design freedom and manufacturing flexibility, which are essential in the current industrial sector (Read et al, 2015;Dong et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Revilla et al [12] has studied the corrosion behaviour of AlSi10Mg alloy and have evidently proved the same. Moreover, it has become one of the most applicable Al alloys for the SLM technique, due to its excellent welding performance, good melt fluidity, low Coefficient of Thermal Expansion (CTE) and high recycling potential, as indicated by Porter [13] and Dong et al [14]. Experimental work by Maamoun et al has showed the recycling potential of AlSi10Mg in particular [15].…”
Section: Introductionmentioning
confidence: 99%